Phosphorus-substituted rhodamines for bioimaging of the lysosomal peroxynitrite in vivo. (May 2022) - Lin, Xiaofeng; Fan, Mengting; Li, Ni; Yang, Jiaojiao; Zhu, Haidan; Chen, Bo; Zhu, Junru; Zhang, Dazhi; Wang, Ting; Cui, Xiaoyan
Abstract: Fluorescence bioimaging the dynamic of reactive oxygen species (ROS) in particular organelles has attracted extensive attention owing to their critical roles in many cellular processes. By tuning the electronic structures of rhodamine through the heteroatom-substitution, the highly oxidative peroxynitrite (ONOO − ) in lysosomes was sensitively tracked by the designed phosphorus-substituted rhodamine (PR) without incorporating any external trigger. The specific and efficient reaction between the designed PR probes (PR1-ONOO and PR2-ONOO ) and ONOO − have ensured the sensitivity and selectivity in the bioimaging of lysosomal ONOO − in vivo . Cancer and normal cells, tumor and normal tissues were distinguished by the fluorescence bioimaging of the lysosomal ONOO − . Moreover, the unique structures and properties of PR ensured sensitively monitoring the dynamic of lysosomal ONOO − monitored in the ferroptosis process. Highlights: Phosphorus-substituted rhodamines (PRs) were designed for ONOO − through a novel strategy. PR probe demonstrates robust selectivity and sensitivity by oxidation of rhodamine scaffold. The probe was developed without lysosomal targeting groups or specific fluorescence triggers. Reliable photostability, solubility, and biocompatibility have ensured their applications. Probe was applied in tracking exogenous and endogenous lysosomal ONOO − in living cells and mice.